In-Vitro Antiproliferative Analysis of Aqueous Leaf Extract from Cardiospermum Halicacabum in Human Hepatocellular Carcinoma Cell Line - Anushya. P; Lakshminarayanan Arivarasu; S. Raghunandha Kumar (The Bioscan, 2025)
Background: Cancer is one of the multi-factorial, multi-faceted, and multi- mechanistic diseases requiring a multi-dimensional approach for its treatment, control and prevention. Many anticancer drugs in clinical use today are derived from natural sources. Cardiospermum halicacabum (C. halicacabum). is a herbaceous plant, extensively dispersed in tropical and subtropical areas of the world. The present study was designed to determine the anti proliferative activity of C. halicacabum aqueous leaf extract on human hepatocellular carcinoma (HepG-2) cells. Method: The leaves of C. halicacabum were extracted with ethanol using soxhlet apparatus. The anti-proliferative activity of C. halicacabum was evaluated by 3-(4,5- dimethylthiazol-2-yl)-2,5-diphenyl-tetrazolium bromide, a yellow tetrazole (MTT) assay and their cell morphological changes was assessed by phase contrast microscope. Results: Our present study showed the anti proliferative activity of Cardiospermum halicacabum at different concentration (25 μg/mL, 50μg/mL,75 μg/mL, 200 μg/mL and 300 μg/mL). The inhibitory concentration (IC-50) value of aqueous extract of Cardiospermum halicacabum was found to be 50 μǥ/ml which is considered to be effective dose. We observed significant morphological changes in Cardiospermum halicacabum treated cells. Conclusion: The aqueous extract of C. halicacabum has confirmed hopeful antiproliferative activity against human hepatocellular carcinoma (HepG-2) cells. In further investigations, to assess its isolates of pure bio active compounds and find out the effectiveness of the C. halicacabum to serve as natural chemotherapeutic agent.